Influence of ball burnishing on residual stress profile of a 15-5PH stainless steel. (May 2016) - Chomienne, V.; Valiorgue, F.; Rech, J.; Verdu, C.
Abstract: Ball-burnishing is a superfinishing process commonly applied to improve the surface integrity (surface roughness, residual stress, microstructure, hardness) of a mechanical component. This paper focuses on the influence of ball-burnishing on residual stress profile of a 15-5PH martensitic stainless steel. After a preparation of the surfaces by turning, various burnishing parameters were investigated to understand their influence on the residual stress profiles in axial and circumferential directions. It is highlighted that burnishing induces an intense and deep compressive layer. Among the ball-burnishing process parameters, the normal force is the most sensitive ones to modify the thickness of the affected layer and the peak of compression in the sub-surface, whereas the speed, the feed and the number of passes have a limited influence on the residual stress profiles.